Effect of early rehabilitation on activities of daily living in patients with aspiration pneumonia. Issue 11 (13th October 2015) - Yagi, Maiko; Yasunaga, Hideo; Matsui, Hiroki; Fushimi, Kiyohide; Fujimoto, Masashi; Koyama, Teruyuki; Fujitani, Junko
Abstract : Aim: To assess the effect of early rehabilitation on improving activities of daily living (ADL) in elderly patients with aspiration pneumonia. Methods: Using the Japanese Diagnosis Procedure Combination inpatient database, we retrospectively analyzed consecutive patients with aspiration pneumonia at admission who received early rehabilitation ( n = 48 201) or did not receive any rehabilitation ( n = 64 357) from July 2010 to March 2013. Early rehabilitation was defined as any type of physical rehabilitation initiated within 7 days after admission. The proportions of improved ADL scores from admission to discharge were compared between the early rehabilitation group and the non‐rehabilitation group using a multivariable logistic regression analysis and instrumental variable analysis. Results: The proportion of improved ADL scores was higher in the early rehabilitation group than in the non‐rehabilitation group (25.4% vs 33.9%; P < 0.001). The multivariable logistic regression analysis showed that the early rehabilitation group exhibited significant improvement in ADL (odds ratio 1.57; 95% confidence interval 1.50–1.64; P < 0.001). The instrumental variable analysis showed that early rehabilitation was associated with increased proportion of improved ADL (risk difference 8.2%; 95% confidence interval 6.9–9.5%; P < 0.001). Conclusions: The present results suggest that early rehabilitation might improve ADL during hospitalization in patients with aspiration pneumonia.Geriatr Gerontol Int 2016; 16: 1181–1187.